Influenza vaccine effectiveness against hospitalizations in children and older adults—Data from South America, 2013–2017. A test negative design. (10th December 2019) - ; Gonzalez, Cecilia; Loayza, Sergio; Vergara, Natalia; Bustos, Patricia; Andrade, Winston; Magda S. Domingues, Carla; Issac Montenegro Renoiner, Ernesto; Tatiane da Silva, Érica; Lima Palmeira, Swamy; Araujo da Silva, Daiana; Carolina de Lacerda Sousa, Ana; et al.
Abstract: Background: In 2013, the Pan American Health Organization established a multi-site, multi-country network to evaluate influenza vaccine effectiveness (VE). We pooled data from five consecutive seasons in five countries to conduct an analysis of southern hemisphere VE against laboratory-confirmed influenza hospitalizations in young children and older adults. Methods: We used a test-negative design to estimate VE against laboratory-confirmed influenza in hospitalized young children (aged 6─24 months) and older adults (aged ≥60 years) in Argentina, Brazil, Chile, Colombia, and Paraguay. Following country-specific influenza surveillance protocol, hospitalized persons with severe acute respiratory infections (SARI) at 48 sentinel hospitals (March 2013–December 2017) were tested for influenza virus infection by rRT-PCR. VE was estimated for young children and older adults using logistic random effects models accounting for cluster (country), adjusting for sex, age (months for children, and age-in-year categories for adults), calendar year, country, preexisting conditions, month of illness onset and prior vaccination as an effect modifier for the analysis in adults. Results: We included 8426 SARI cases (2389 children and 6037 adults) in the VE analyses. Among young children, VE against SARI hospitalization associated with any influenza virus was 43% (95%CI: 33%, 51%) for children who received two doses, but was 20% (95%CI: −16%, 45%) and not statistically significant for those who received one dose in a given season. Among older adults, overall VE against SARI hospitalization associated with any influenza virus was 41% (95%CI: 28%, 52%), 45% (95%CI: 34%, 53%) against A(H3N2), 40% (95%CI: 18%, 56%) against A(H1N1)pdm09, and 20% (95%CI: −40%, 54%) against influenza B viruses. Conclusions: Our results suggest that over the five-year study period, influenza vaccination programs in five South American countries prevented more than one-third of laboratory confirmed influenza-associated hospitalizations in young children receiving the recommended two doses and vaccinated older adults.